2020
DOI: 10.1088/1361-6595/ab5ad5
|View full text |Cite
|
Sign up to set email alerts
|

Negative electric potential in a cylindrical plasma column with magnetized electrons

Abstract: The possibility of creating adjustable electric fields in plasma opens up a wide range of applications for plasma technologies. However, the question with regards to the conditions, under which the plasma potential along the magnetic field line, resting on the electrode, repeats the potential of this electrode, turns out to be quite complex. In the present paper, an axially symmetric system with a magnetic field directed along an axis is considered. At the ends of the system, there are electrodes with a given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 38 publications
6
22
0
1
Order By: Relevance
“…2019; Poulos 2019; Liziakin et al. 2020). Beyond the present investigations in quiescent regimes, the influence of large-scale, low-frequency fluctuations of the plasma parameters usually observed in plasma columns on the efficiency of the plasma flow drive is also a crucial question related to the self-organization in plasmas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019; Poulos 2019; Liziakin et al. 2020). Beyond the present investigations in quiescent regimes, the influence of large-scale, low-frequency fluctuations of the plasma parameters usually observed in plasma columns on the efficiency of the plasma flow drive is also a crucial question related to the self-organization in plasmas.…”
Section: Discussionmentioning
confidence: 99%
“…We show that the rotation profile is set by the local value of the electric drift and that current injection modifies the plasma potential profile. Several recent theoretical models have been developed to understand how biased electrodes modify the potential distribution in strongly or weakly magnetized plasma columns (Curreli & Chen 2014; Gueroult, Rax & Fisch 2019; Poulos 2019; Liziakin, Gavrikov & Smirnov 2020). Our experimental investigation provides a set of experimental data in the weakly magnetized regime, which complements the work of Jin et al.…”
Section: Introductionmentioning
confidence: 99%
“…2019 a ; Liziakin et al. 2020). Therefore, it will be further assumed that the plasma conductivity across the magnetic field is determined by the transport of ions.…”
Section: Ohm's Lawmentioning
confidence: 99%
“…Liziakin et al. (2020) considered the formation mechanism of a negative potential on the axis of a cylindrical plasma column immersed in a magnetic field. The formula was obtained with which it is possible to estimate the plasma column potential.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a necessary condition for potential control along field lines is τ 1. On the latter, Liziakin et al showed considering the sheath formed in front of a negatively biased electrode that the combination of the plasma perpendicular conductivity σ ⊥ and the ion saturation current sets a lower limit on the minimal plasma potential φ p < 0 one can expect from applying a negative bias φ e < φ p [34]. Building on this finding, the same authors recently showed that the addition of thermionic emission from a negatively biased electrode can lower further the plasma potential φ p at the expense of the voltage drop across the sheath φ p − φ e [35], which is consistent with earlier theoretical work [36] and observations [37].…”
Section: Introductionmentioning
confidence: 99%